1970
DOI: 10.1063/1.1673749
|View full text |Cite
|
Sign up to set email alerts
|

Classical Aspects of Energy Transfer in Molecular Systems

Abstract: The decay time of the luminescence of a molecule S in front of a metal mirror depends markedly on its distance from the mirror. This phenomenon is quantitatively explained by considering the radiation field of this dipole, given by Hertz classical equation. This field arrives at the molecule, after being reflected at the mirror, with a retardation of the order of 10−15 sec. The decay time of the luminescence depends on the phase shift produced by this retardation, and thus on the ratio of the distance of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
303
1
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 616 publications
(315 citation statements)
references
References 18 publications
10
303
1
1
Order By: Relevance
“…The same results happen when we place the emitter in the cavity [152,153]. As the cavity itself can have different scales, shapes, and components, only specific modes of EM will be supported [154].…”
Section: Weak Coupling Conditions Of Cavity-qedmentioning
confidence: 55%
“…The same results happen when we place the emitter in the cavity [152,153]. As the cavity itself can have different scales, shapes, and components, only specific modes of EM will be supported [154].…”
Section: Weak Coupling Conditions Of Cavity-qedmentioning
confidence: 55%
“…This phenomenon was first observed by Drexhage 26 and was theoretically explained by several authors. [29][30][31] As the distance decreases further to the order of ∼50 Å to 100 Å, the radiative ion starts experiencing the electromagnetic field associated with surface plasmons. This decay has been observed experimentally and discussed earlier.…”
Section: Radiative Lifetime Of An Optically Active Ion Near a Metallimentioning
confidence: 99%
“…It has previously been reported that gold quenches lanthanide luminescence. 23 However, as such quenching is distance dependent, we proposed that our design would minimise any such quenching due to the presence of the C 12 spacer between 1ÁEu and the surface. To establish this, the delayed emission of 1ÁEu and 1ÁEuÁ2 and 1ÁEuÁ3 was recorded upon excitation at 281 nm.…”
mentioning
confidence: 99%